2022
DOI: 10.3390/antiox11101992
|View full text |Cite
|
Sign up to set email alerts
|

Alhagi maurorum Ethanolic Extract Rescues Hepato-Neurotoxicity and Neurobehavioral Alterations Induced by Lead in Rats via Abrogating Oxidative Stress and the Caspase-3-Dependent Apoptotic Pathway

Abstract: This work investigated the probable protective effect of an Alhagi maurorum ethanolic extract on the hepatotoxicity and neurotoxicity accompanied by neurobehavioral deficits caused by lead in rats. Rats in four groups were orally administered distilled water, ethanolic extract of A. maurorum (300 mg/kg BW daily), lead (100 mg/kg BW daily for 3 months), and lead + A. maurorum extract. The results demonstrated that lead exposure resulted in elevated locomotor activities and sensorimotor deficits associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
(95 reference statements)
1
1
0
Order By: Relevance
“…The results of this study showed a significant decline in the level of GSH and an increase in lipid peroxidation in rats exposed only to Pb in relation to control. These findings are in agreement with Saber et al (2022), which study reported oxidative stress Pb induced. These outcomes may be a result of Pb's high affinity for the SH groups from GSH, resulting in oxidative stress condition (Manoj Kumar et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…The results of this study showed a significant decline in the level of GSH and an increase in lipid peroxidation in rats exposed only to Pb in relation to control. These findings are in agreement with Saber et al (2022), which study reported oxidative stress Pb induced. These outcomes may be a result of Pb's high affinity for the SH groups from GSH, resulting in oxidative stress condition (Manoj Kumar et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…Following the extraction, the quality of RNA was evaluated by a NanoDrop® ND-1000 Spectrophotometer (NanoDrop Technologies, Delaware, USA). Subsequently, synthesis of cDNA was achieved through using the HiSenScript™ RH (-) cDNA Synthesis kit (iNtRON Biotechnology Co., South Korea) ( Al-Shahat et al, 2022 , Saber et al, 2022 ). Analysis of gene expression was conducted using qRT-PCR (Agilent Stratagene, USA) by 5x HOT FIRE Pol EvaGreen qPCR Mix Plus (Solis BioDyne, Tartu, Estonia), according to supplier's directions.…”
Section: Methodsmentioning
confidence: 99%